Cord factor producer Mycobacterium abscessus subsp. bolletii in asymptomatic immunocompetent host sputa samples (Brazilian Journal of Pharmaceutical Sciences, 2022)
We report a case of Mycobacterium abscessus subsp. bolletii colonization in upper respiratory tract of an immunocompetent patient, who was misdiagnosed as tuberculosis by Acid Fast Bacilli (AFB) and cord factor formation observed directly from the sputa culture in liquid medium. This fact reflected a significant impact on the individual case’s life and showed the importance to identify the mycobacteria isolated from clinical sample at species level, and to determine the true implication of nontuberculous mycobacteria (NTM) detected in clinical samples.